What is the added value of applying a gender-transformative approach within a livelihoods intervention, in terms of accelerating lasting transformations in gender equality, food security and economic well-being? - Mohanraj, Pranati (CARE, 2023)
This paper presents a comparative study, conducted by CARE, of a gender-transformative model for gender equality, compared against a typical gender-sensitive approach (‘gender light’), both of which were integrated into a program for women’s economic empowerment intervention, which included agriculture development and group-based savings and loans in Burundi. The gender-transformative (GT) approach was based on Freirean principles and followed an iterative cycle of critical reflection and action to analyze gender norms and build women’s solidarity and collective action. It also engaged men equally in the processes of critical reflection on harmful gender norms. A three-arm mixedmethods impact evaluation was conducted, comparing the GT model with the ‘gender light’ model and a control (no gender focus). Cost-benefit data were collected from two main sources: project documentation and primary data from program participants. The GT model yielded a return of 5:1, compared to 3:1 return for a ‘gender light’ model and a 2:1 return for a model with no gender focus. The findings indicate that of the three models, the GT model is the most economically viable. Additionally, the evidence suggests that the ‘gender light’ approach initiated some important community discussions, but the GT approach catalyzed more sustainable and far-reaching gender-norm changes alongside significant achievements in improving household food security and economic well-being. We suggest that investing in a gender-transformative approach within a livelihoods intervention may have more far-reaching and sustainable effects accelerating lasting transformations in gender equality, food security and economic well-being.